CRISPR-Cas9 driven structural elucidation of the heteroexopolysaccharides from Paenibacillus polymyxa DSM 365. (15th July 2023) - Schilling, Christoph; Klau, Leesa J.; Aachmann, Finn L.; Rühmann, Broder; Schmid, Jochen; Sieber, Volker
Abstract: Paenibacillus polymyxa is a Gram-positive soil bacterium known for producing a wide range of exopolysaccharides. However, due to the biopolymer's complexity, structural elucidation has so far been inconclusive. Combinatorial knock-outs of glycosyltransferases were generated in order to separate distinct polysaccharides produced by P. polymyxa . Using a complementary analytical approach consisting of carbohydrate fingerprints, sequence analysis, methylation analysis as well as NMR spectroscopy, the structure of the repeating units of two additional heteroexopolysaccharides termed paenan I and paenan III were elucidated. Results for paenan I identified a trisaccharide backbone consisting of 1➔4-β-d -Glc, 1➔4-β-d -Man and a 1, 3, 4-branching β-d -Gal residue with a sidechain comprising of a terminal β-d -Gal 3, 4-Pyr and 1➔3-β-d -Glc. For paenan III, results indicated a backbone consisting of 1➔3-β-d -Glc, 1, 3, 4-linked α-d -Man and 1, 3, 4-linked α-d -GlcA. NMR analysis indicated monomeric β-d -Glc and α-d -Man sidechains for the branching Man and GlcA residues respectively. Graphical abstract: Unlabelled Image